2007
DOI: 10.1111/j.1574-6941.2007.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term dynamics of catabolic plasmids introduced to a microbial community in a polluted environment: a mathematical model

Abstract: The long-term dynamics of mobile plasmids in natural environments are unclear. This is the first study of the long-term dynamics of introduced plasmids with xenobiotic degradation abilities using a mathematical model that describes the horizontal gene transfer (HGT) of plasmids into indigenous bacteria via conjugation. We focussed on negative feedback between the spread of plasmids and their selective advantage, i.e. the severe competition between plasmid-bearing and plasmid-free bacteria resulting from a decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Furthermore, many natural plasmids repress expression of their self-transfer functions (Firth et al, 1996;Lawley et al, 2004). These observations are surprising given that increased rates of conjugation aid plasmids in invading and persisting within host populations, as demonstrated by this work and others' (Stewart and Levin, 1977;Dionisio et al, 2002;De Gelder et al, 2007Miki et al, 2007). Here we show that, in a population of plasmid-bearing cells, a variant plasmid with a decreased conjugation rate can give its hosts a competitive edge.…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, many natural plasmids repress expression of their self-transfer functions (Firth et al, 1996;Lawley et al, 2004). These observations are surprising given that increased rates of conjugation aid plasmids in invading and persisting within host populations, as demonstrated by this work and others' (Stewart and Levin, 1977;Dionisio et al, 2002;De Gelder et al, 2007Miki et al, 2007). Here we show that, in a population of plasmid-bearing cells, a variant plasmid with a decreased conjugation rate can give its hosts a competitive edge.…”
Section: Discussionmentioning
confidence: 73%
“…The conservation of pixR in the IncX4 plasmids suggests that this gene provides an evolutionary advantage for mcr-1-bearing IncX4 in nature. pixR increases the transfer capability of IncX4 plasmids and a high rate of conjugation usually helps plasmids invade bacterial populations (19,20,37). Therefore, here we investigated the role of pixR in the persistence and invasion of mcr-1bearing IncX4 plasmids to better understand their prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted August 6, 2021. ; https://doi.org/10.1101/2021.08.04.455183 doi: bioRxiv preprint plasmids and a high rate of conjugation usually helps plasmids invade bacterial populations (19,20,37). Therefore, here we investigated the role of pixR in the persistence and invasion of mcr-1bearing IncX4 plasmids to better understand their prevalence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrated that the selection and growth of donor and transconjugant cells were dependent on the presence of sufficiently high concentrations of the specific substrate ( Ravatn et al., 1998 ). To predict the long-term dynamics of catabolic plasmids in a polluted environment, a mathematical model was developed that considered the negative feedback between plasmid spread and selective advantage: when catabolic genes are highly spread, the OMP concentration will decrease faster, thereby lowering the selective advantage of plasmid-bearing bacteria ( Miki et al., 2007 ). Thus, in order to achieve long-term OMP degradation, it is necessary to find the right plasmid spread efficiency in order to maintain constant, low pollutant concentrations, as the degrading microbial community remains more stable when OMP degradation occurs slowly.…”
Section: Transfer Of Catabolic Genes As a Bioaugmentation Strategy Inmentioning
confidence: 99%